(3GdGeGf ef GNWGQ GdGSaGQ hGdGReGfs - (3CHh GdbGSe Ydj Hf ehSi Hf LYaQ Hf eMeO, GHf GdWGhhS GdYdhj,J (B664 (3g` s ((3MSjf Hf YeGQ s)
(3ChdgG (B:s
(3GdaUd GdChd ajeG JPcQg ef YRe GdGfSGf hfjJg dSaQg Ydi ENJdGa EQGOJg s
(3BNQgG (B:s
(3GdHGH GdQGHY YTQ ai hUa GdadGM ef GdYQb GdeOjfi EPG JhdO ai GdHOf GdJi ef SdGeI GdfaS hUMI GdHOf Efg Ydi eG jTGA bOjQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B166s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs